Membantai Kabau Nan Gadang: the localwisdom of Nagari Alam Pauh Duo - Desmailafrita Desmailafrita; Fitri Eriyanti; Erianjoni Erianjoni (Fakultas Ilmu Pendidikan UNP)
Membantai Kabau Nan Gadang is the traditional herritage from ancestors with a purpose planting patterns simultaneously. In a Minangkabau proverb is said “ka sawah basamo-samo, ka ladang badakok-dakok”. The history of this traditional ceremony is a form of trustworthiness of the local community which is a part of the local wisdom in farming activity for increasing sufficiency of food through planting patterns simultaneously. The purposes of this research are : background of the traditional ceremony and the implementation process. This research is qualitative research. It was conducted with the ethnography approach. The results of this research: The history of this traditional ceremony was a symbol peace between ancestors in snatching area, and reasons of the society defend: belief of nature, the history of Nagari Alam Pauh Duo, and collective awareness of niniak mamak. The process in two days. The first day is slaughtering buffalo. The second day is eating bajamba surang-surang, watching regional art, agriculture department officer gives instructions and reading amad. The last step is closing by praying together.